2009
DOI: 10.1089/ten.tea.2009.0089
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the αGal Epitope on the Response to Small Intestinal Submucosa Extracellular Matrix in a Nonhuman Primate Model

Abstract: The Galalpha1,3Galbeta1,4GlcNAc-R (Gal) epitope is a major factor in the hyperacute rejection of pig organ transplants in primates. Biologic scaffold materials used for tissue reconstruction and composed of xenogeneic extracellular matrix (ECM) may contain the Gal epitope. However, the effect of this epitope upon the host response is controversial. The present study investigated the effect of the Gal epitope upon the host response to a porcine-derived ECM in an African Green monkey (Cholrocaebus aethiops) abdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(97 citation statements)
references
References 55 publications
2
95
0
Order By: Relevance
“…28 However, when present in sufficiently small quantities, neither DNA nor the a-gal epitope has been associated with poor outcomes in vivo. 29,30 The objective of the present study was to characterize the adipose ECM material resulting from three distinct methods of decellularization-one method developed and optimized by the authors and two previously published methods-to determine the most effective method for the derivation of an adipose tissue ECM scaffold that was largely free of potentially immunogenic cellular content, including DNA and cytoplasmic lipid, while retaining adipose tissue-specific structural and functional components. The efficacy of removal of cellular content, the effect upon ultrastructure, maintenance of several ECM components and growth factors, and the ability of the resulting material to support the in vitro growth and differentiation of adipose-derived stem cells (ADSCs) toward an adipogenic lineage were investigated for each method.…”
mentioning
confidence: 99%
“…28 However, when present in sufficiently small quantities, neither DNA nor the a-gal epitope has been associated with poor outcomes in vivo. 29,30 The objective of the present study was to characterize the adipose ECM material resulting from three distinct methods of decellularization-one method developed and optimized by the authors and two previously published methods-to determine the most effective method for the derivation of an adipose tissue ECM scaffold that was largely free of potentially immunogenic cellular content, including DNA and cytoplasmic lipid, while retaining adipose tissue-specific structural and functional components. The efficacy of removal of cellular content, the effect upon ultrastructure, maintenance of several ECM components and growth factors, and the ability of the resulting material to support the in vitro growth and differentiation of adipose-derived stem cells (ADSCs) toward an adipogenic lineage were investigated for each method.…”
mentioning
confidence: 99%
“…This immune activation does not appear to alter the host response to the scaffolds (37). If necessary, further reduction of the Gal epitope can be achieved by enzymatic cleavage during processing (38,39) or by obtaining tissues from genetically modified pigs that lack the Gal epitope (37,40).…”
Section: Figurementioning
confidence: 99%
“…Since the !-gal epitope is present both on cells and on glycoproteins of the ECM, binding of anti-Gal to these epitopes on the ECM may result in immune mediated destruction of the ECM. A study addressing this issue has been performed by implantation of ECM scaffold, prepared from porcine intestinal submucosa, in an anti-Gal producing monkey [54]. This study has indicated that despite presentation of !-gal epitopes by this ECM, and the resulting elevation in anti-Gal titer, no adverse effects were observed upon tissue remodeling and regeneration of the connective tissue [54].…”
Section: Incorporation Of !-Gal Nanoparticles Into Decellularized Tismentioning
confidence: 99%
“…A study addressing this issue has been performed by implantation of ECM scaffold, prepared from porcine intestinal submucosa, in an anti-Gal producing monkey [54]. This study has indicated that despite presentation of !-gal epitopes by this ECM, and the resulting elevation in anti-Gal titer, no adverse effects were observed upon tissue remodeling and regeneration of the connective tissue [54]. However, in decellularized organs containing epidermal components, ECM that includes basement membrane expresses much higher amounts of !-gal epitopes, primarily because of the abundance of laminin that carries 50-70 !-gal epitopes per molecule and thus readily binds anti-Gal [55].…”
Section: Incorporation Of !-Gal Nanoparticles Into Decellularized Tismentioning
confidence: 99%